Planning and designing the IP broadcast facility a new puzzle to solve - Olson, Gary (Burlington, MA Focal Press, 2014)
"The transition to computer-based technologies and file-based workflows is one of the most significant changes the broadcast and production industry has seen. Media is produced for multiple delivery platforms: Over the Air, Over the Top, large screen displays, cable, satellite, web, digital signage, tablets, and smartphones. These changes impact all aspects of creation, production, media management, technical operations, business processes, and distribution to end users. Of all the books and papers discussing storage mapping, packet transport, and compression algorithms, none puts all the pieces together and explains where these fit into the whole environment. Planning and Designing the IP Broadcast Facility is the first to provide a comprehensive understanding of the technology architecture, physical facility changes, and--most importantly--the new media management workflows and business processes to support the entire lifecycle of the IP broadcast facility from an engineering and workflow perspective"-- Provided by publisher.
Keywords: Webcasting; Internet radio broadcasting; Digital media; Communication and technology